Factors Associated with Smoking Habits in Rt 11, 25 and 35 Paal Merah Village Paal Merah I Health Center Work Area Jambi City - Dalil, Muhammad; Sianipar, Sri Natalia; Ramadani, Anisa Femilia; Rahayu, Putri; Varid, M. Raihan Octario; Amir, Andy (Journal of Midwifery and Nursing, 2024)
Smoking habits are a fundamental health problem in various countries and the increasing number of people who smoke so that the negative impact is increasing. This type of research is quantitative analytic with a Cross Sectional study design using primary data PIS-PK questionnaire with a population of Rt 11, 25 and 35 Paal Merah Village, there is also a sample size of 100 people. Calculation of sample size using random sampling data analysis was carried out by frequency analysis, bivariate chi square analysis. Peeltiian results show the age variable there is no relationship between age and smoking habits. Education level has no relationship with smoking behavior with OR 0.575. Socioeconomic level has no relationship with smoking behavior with OR 0.383. Gender variable has no relationship with smoking behavior. In conclusion, there is no significant relationship between age, education level, socioeconomic level, and gender with smoking habits. for health workers in the Paal Merah 1 Puskesmas work area to increase educational and counseling efforts to the community regarding the dangers of smoking and the importance of maintaining health.